Marca notória: um estudo sobre a aquisição e perda de distintividade de marcas decorrentes de sua notoriedade - Mello, Fernanda Fujita de Castro (2010)
The present study aims at analyzing two empiric phenomena resulting from the notoriety of a mark: the attainment and the loss of trademark distinctiveness. Firstly, it aims to introduce the institute of the mark as a distinctive sign, demonstrating that the distinctiveness is a condition of validity for the grant thereof. After defining the institute, the attainment of notoriety by the mark is analyzed, being the object of the present study the notorious mark as the category, and the well-known mark and high-reputation mark as the types. The legal provision and the scope of protection of notorious marks are broached, as well as the main consequences of trademark notoriety. Having made this introduction, the present study discusses the phenomena of attainment and loss of trademark distinctiveness resulting from the notoriety thereof. The first of them is studied by the theory of secondary meaning, and its occurrence is analyzed in all systems of trademark attainment. Emphasis is given to the expressions originally non distinctive and which are susceptible of attainment of secondary meaning, being therefore susceptible to registration as a mark. Next, the phenomenon of loss of trademark distinctiveness resulting from its distinguishability is analyzed, the phenomenon known as trademark degeneration or trademark degeneracy. Since it deals with a slow process, and almost always irreversible, some indicator signs of trademark degeneration are studied, as well as customary forms used to avoid it. Finally, a few judicial and administrative decisions involving the referred to phenomena are analyzed, seeking to exemplify some forms found for proving and identifying the attainment of secondary meaning and trademark degeneration empirically, emphasizing the position of the Courts and the INPI (the Brazilian Patents and Trademarks Office) in relation to the matter